PENYELESAIAN KREDIT MACET ANTARA BANK BPR PIJER PODI KEKELENGEN DENGAN NASABAH PADA PT. BPR PIJER PODI KEKELENGEN DI CABANG SIMPANG POS MEDAN - Oktanika, Edward; Jayakusuma, Zulfikar; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Bad Credit Settlement is action resolve a situation where the bank customer is unable to pay partially or completely of the liability to bank as promised between the bank customer and bank. Bank is a business entity that collects funds from the public in the form of saving and distributes in to the public in the form of credit in order to improve the standard of living of the people. Act number 10 of 1998 about banking, classifies bank in two types commercial bank and BPR. BPR is bank financial institutions that accept deposits only in the form of deposits, savings or other form channel funds in the form of credit to improve the standard of living of people carrying out business activities through conventional or syariah principles. In its activities it does not provide services and taffict payment. Bank Customer are parties who use bank service.This type of research is an empirical juridical research or sociological law research, namely a research approach that emphasizes the legal aspect regarding the subject matter to be discussed, associated with the realitiesin the field. This research was conducted in the office PT. BPR Pijer Podi Kekelengen branch company Simpang Pos Medan. The simple and population are customer and bank that etered into a credit aggrement.source of data obtained based on primery and secondary data. Data collection techinques in research using observation, questionnaires, interview, and library studies.Of the research, there are two things that can be concluded, first the settlement of bad credit at bank PT. BPR Pijer Podi Kekelengen branch Simpang Pos Medan. Second, the rights and obligations of the parties in the credit agreement between bank and bank customer at bank PT. BPR Pijer Podi Kekelengen branch company Simpang Pos Medan.Keyword: bad credit settlement – bank – bank customer